A literature review on correlation between HPV coinfection with C. trachomatis and cervical neoplasia - coinfection mediated cellular transformation. (July 2022) - Kumari, Seema; Bhor, Vikrant M.
Abstract: Cervical cancer is the fourth most common cause of mortality worldwide. Persistent infection with high-risk human papillomaviruses (hrHPV) is a known significant risk factor in cervical neoplasia development (CN). Though HPV contributes to carcinogenesis, other factors provide an ideal niche for persistence of HPV, especially, coinfection with Chlamydia trachomatis (CT) which has been linked to CN development. CT infection is associated with inflammation, cell proliferation, EMT transition and anti-apoptotic processes. To better understand the correlation between HPV-CT coinfection and CN development, a literature review was conducted on the prevalence of HPV-CT coinfection focusing on the role of infection-induced inflammation as HPV-CT coinfection creates an environment for cellular transformation, activates an innate immune response and triggers EMT transition. Moreover, inflammation plays a crucial role in developing neoplasia as there is a decrease in effector cells and a change in the levels of players like ROS and miRs. CT infection induces chronic inflammation followed by cervical epithelial cell damage and increases susceptibility to HPV infection which may lead to cellular transformation. The literature search was performed based on a comprehensive investigation of publications in the PubMed journal database and Scopus, on the development of CN. We have reviewed the prevalence of HPV-CT infection and the factors increasing the risk of developing CN. Highlights: Chlamydia trachomatis infection may increase the persistence of HPV. Prevalence of HPV- Chlamydia trachomatis coinfection is higher in younger women. HPV-CT coinfection creates an environment for cellular transformation.